2019
DOI: 10.3390/ani9090603
|View full text |Cite
|
Sign up to set email alerts
|

Litter Survival Differences between Divergently Selected Lines for Environmental Sensitivity in Rabbits

Abstract: Simple SummaryTwo rabbit lines are divergently selected for increasing or decreasing the variability of litter size at birth. Decreasing the litter size variability produces more resilient females with less sensitivity to diseases, being an indirect selection way to improve environmental sensitivity. The kits’ survival rate at weaning was higher in the homogeneous line. Moreover, this line led to a greater uniformity of the kits’ weight at weaning, although the weight variability at birth was higher, which cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 25 publications
4
10
1
Order By: Relevance
“…Primiparous does have litters with the highest number and percentage of kits below 45 g, increasing the chance of kits mortality (Szendr} o and Barna 1984;Poigner et al 2000a,b). In fact, the probability of individual survival is related to birth weight, as the kits with lower birth weight have a lower probability of survival (Agea et al 2019). This was observed also in the current study, although the effect of parity was not statistically significant on MR.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Primiparous does have litters with the highest number and percentage of kits below 45 g, increasing the chance of kits mortality (Szendr} o and Barna 1984;Poigner et al 2000a,b). In fact, the probability of individual survival is related to birth weight, as the kits with lower birth weight have a lower probability of survival (Agea et al 2019). This was observed also in the current study, although the effect of parity was not statistically significant on MR.…”
Section: Discussionsupporting
confidence: 76%
“…Litters of does in the 6th parturition were the most homogeneous, while the 3rd, 4th and 7th included few light kits and many heavy kits. It is well known that there is a positive correlation between survival and uniformity of weight at birth, without affecting individual and LW (Agea et al 2019). In fact, Bolet et al (2007) found a negative correlation between LS and mn-BAW and an increase in mn-BAW variance in larger litters.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, it correlated low birth weights with lower survival, although many other environmental factors exacerbate this effect. Agea et al [ 18 ] reported higher weights for the LW variable, and Fadare and Fatoba [ 19 ] presented lower weights than those found in this work.…”
Section: Resultscontrasting
confidence: 59%
“…Therefore, there is an important increase in the mobilization of dam’s body reserves, which leads them to lose body condition (review by Castellini et al [ 25 ]). In this sense, we also observed a decrease in body condition between 10 days after delivery and weaning in both lines, although the decrease is slightly higher in the low line due to a large number of kits at weaning [ 18 ].…”
Section: Discussionmentioning
confidence: 92%
“…Uniformity in litter size and body weight has been related to immune response and resistance to diseases (see review [ 17 ]). Additionally, we have found that selection for reducing residual variance of litter size increases litter size without affecting the individual weight neither at birth nor at weaning [ 18 ].…”
Section: Discussionmentioning
confidence: 99%